2015
DOI: 10.1155/2015/917156
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ACE Retards Tau Hyperphosphorylation and Signs of Neuronal Degeneration in Aged Rats Subjected to Chronic Mild Stress

Abstract: With increasing life expectancy, Alzheimer's disease (AD) and other types of age-associated dementia are on the rise worldwide. Treatment approaches for dementia are insufficient and novel therapies are not readily available. In this context repurposing of established drugs appears attractive. A well-established class of cardiovascular drugs, which targets the angiotensin II system, is such a candidate, which currently undergoes a paradigm shift with regard to the potential benefit for treatment of neurodegene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 42 publications
3
11
0
1
Order By: Relevance
“…Some clinical and meta-analysis studies have also shown that ACEIs reduce the progression and risk of AD [ 184 , 185 , 186 , 187 ]. This result has also been observed in several animal model studies [ 188 , 189 , 190 ]. However, in one meta-analysis study, ACEIs had no effect on cognitive decline [ 191 ], and some studies have shown a negative effect of ACEIs in in-vivo AD models [ 192 , 193 , 194 ].…”
Section: Adiponectin-associated Therapeutic Strategy Against Ad Insupporting
confidence: 84%
“…Some clinical and meta-analysis studies have also shown that ACEIs reduce the progression and risk of AD [ 184 , 185 , 186 , 187 ]. This result has also been observed in several animal model studies [ 188 , 189 , 190 ]. However, in one meta-analysis study, ACEIs had no effect on cognitive decline [ 191 ], and some studies have shown a negative effect of ACEIs in in-vivo AD models [ 192 , 193 , 194 ].…”
Section: Adiponectin-associated Therapeutic Strategy Against Ad Insupporting
confidence: 84%
“…Some ACEIs even reduced Aβ peptide level in animal models of AD ( AbdAlla et al, 2013 ). Moreover, ACEIs showed beneficial effect in reducing AD signs and symptoms ( Dong et al, 2011 ; Tota et al, 2012 ; AbdAlla et al, 2015 ). Administration of perindopril (ACEI) has shown an instrumental effect in increasing density of normal neurons and improving learning and memory ( Hou et al, 2008 ).…”
Section: Renin Angiotensin System and Alzheimer’s Disease: Animal Stumentioning
confidence: 99%
“…This catabolism is mainly mediated through IRAP activation (vasopressin, oxytocin, somatostatin and cholecystokinin) , but ACE contributes to the catabolism of other metabolites, such as substance P, neurotensin, dynorphin and encephalin . ACE participates in neurodegeneration induced by environmental stress, a major factor of AD pathology. Glutamate neurotoxicity and neurodegeneration are increased by genes which downregulate microtubule‐associated protein 2 ( Map2 ), synuclein‐gamma ( Sncg ) and glutamate decarboxylase 2 ( Gad2 ) . This downregulation occurs through angiotensin 1 receptor (AT1R) activation.…”
Section: The Brain Renin–angiotensin Systemmentioning
confidence: 99%
“…This downregulation occurs through angiotensin 1 receptor (AT1R) activation. In a rat model of chronic unpredictable stress, ACE hippocampal upregulation and tau hyperphosphorylation could be averted by treatment with central‐acting captopril . AT1 receptors in brain vessels control cerebrovascular flow and vessel autoregulation and thus contribute to regulate oxygen and nutrient supply to the brain . Overactivation of AT1 receptors in neurons blocks hippocampal long‐term potentiation , increases oxidative stress and promotes neuroinflammation .…”
Section: The Brain Renin–angiotensin Systemmentioning
confidence: 99%